Factors that Influence Healthcare Provider Recommendation of HPV Vaccination. Issue 7 (September 2022) - Btoush, Rula; Kohler, Racquel Kelly; Carmody, Dennis P.; Hudson, Shawna V.; Tsui, Jennifer
Purpose : This study examined factors associated with healthcare providers' (HCPs') recommendation of HPV vaccination for younger and older adolescents.Methods : This is a cross-sectional study, using web-based survey of HCPs in New Jersey in 2018. The study outcome was a dichotomous measure of HCPs' recommendation of the HPV vaccine. The study predictors included practice characteristics (i.e., proportions of race/ethnicity, age groups, insurance type, and VFC recipients) and HCP's characteristics (i.e., specialty and perceived knowledge, effectiveness, concerns, parent- and system-related barriers, and facilitators). Data analysis included logistic regression models using separate blocks for practice and provider characteristics, followed by a backward stepwise approach to determine the surviving predictors.Results: Respondents (N=390) included physicians (75%) and nurse practitioners (25%), specialized in pediatrics (62%), family medicine (20%), and women's health (18%). The HCPs' recommendation rates for HPV vaccination were 56% for younger adolescents (11–13 years old) and 73% for older adolescents (14–17 years old). For younger adolescents, the recommendation rates were significantly higher in practices with higher proportions of younger adolescent, Black and Hispanic patients; among pediatric providers; and with HCPs' higher levels of knowledge and lower levels of concern about the vaccine. For older adolescents, the rates were significantly higher in practices with higher proportions patients who are Hispanic, privately insured, and VFC recipients; among pediatric providers; and with HCPs' higher levels of knowledge and lower levels of concern about the vaccine as well as higher levels of facilitators for recommending the HPV vaccine.Conclusions: Interventions targeting HCPs need to focus on improving their knowledge regarding the vaccine, reduce their concerns around its safety, and utilize facilitators strategies, particularly among non-pediatric providers.